2016
DOI: 10.1111/jpc.13409
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of dextrose gel in the management of neonatal hypoglycaemia

Abstract: Dextrose gel is effective in the management of neonatal hypoglycaemia in the postnatal ward setting, reducing admission to NICU and mother-infant separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 12 publications
(17 reference statements)
1
25
0
3
Order By: Relevance
“…The follow-up study conducted by the same group questioned the previous promising results by showing that it did not impact neurodevelopmental outcomes (63). Several studies have concluded that oral dextrose gel is suitable to treat hypoglycemia in stable infants, who can be fed (59)(60)(61)(62). Dextrose gel is being favored not only for prevention and treatment of hypoglycemia but for promoting breast feeding and bonding of mothers and babies.…”
Section: Newer Approaches To Management Of Neonatal Hypoglycemiamentioning
confidence: 99%
“…The follow-up study conducted by the same group questioned the previous promising results by showing that it did not impact neurodevelopmental outcomes (63). Several studies have concluded that oral dextrose gel is suitable to treat hypoglycemia in stable infants, who can be fed (59)(60)(61)(62). Dextrose gel is being favored not only for prevention and treatment of hypoglycemia but for promoting breast feeding and bonding of mothers and babies.…”
Section: Newer Approaches To Management Of Neonatal Hypoglycemiamentioning
confidence: 99%
“…Treatment of neonatal hypoglycaemia with oral dextrose gel has been shown to result in hypoglycaemia reversal, reduced admission to NICU for hypoglycaemia and reduced formula feeding at 2 weeks of age . Therefore, treatment with dextrose gel has the potential to not only keep mothers and babies together in the first days after birth but also to reduce costs associated with admission to NICU and hypoglycaemia‐associated brain damage . As a result, treatment with dextrose gel is becoming more widespread …”
mentioning
confidence: 99%
“…Therefore, treatment with dextrose gel has the potential to not only keep mothers and babies together in the first days after birth but also to reduce costs associated with admission to NICU and hypoglycaemia‐associated brain damage . As a result, treatment with dextrose gel is becoming more widespread …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dextrose gel is now being used in some settings as first-line treatment for neonatal hypoglycemia 12, 13 . However, because the primary objective of treatment of neonatal hypoglycemia is to prevent brain injury, it is important to determine whether treatment with dextrose gel is associated with any beneficial or adverse effects on later development.…”
mentioning
confidence: 99%